Estabelecimento de critérios inovadores para a quantificação da precipitação para a região coberta pelo radar meteorológico de Maceió - Ihadua, Isidro Metódio Tuleni Johanes (2016)
The main objective of this study is to contribute for the stablishment of new criteria to quantify the precipitation for the área covered by the meteorological radar of Maceió, Alagoas. Radar, disdrometer and pluviometer data were used to calculate the drop diameter distribution and radar images were converted into pluviometric data with the purpose of obtaining the Z-R, KDP and ZDR-R relations necessary to classify the nature of the hydrometeors and quantify the precipitation. During the elaboration of this study, it was neither possible to obtain the KDP-R relation nor to calibrate the accumulated 24 hour rain rate in order to verify the efficiency of the estimative due to the occurrence of a strong El Nino (in 2015). Generally, El Nino events causes a decrease in the precipitation of the Northeaster’s rainy season and, rain rates greater than 30 mm/hr or sequences of data to obtain the 24 hr totals (to check the efficiency of the calibration) were not available. However, this drawback did not fade the importance of the study because it was possible to obtain the polarimetric estimates ZDR (ZDR-R relation) and the precipitation at every 10 minutes. The outcomes resulting from the polarimetric ZDR relation and calibration with instantaneous rates are of expressive scientific relevance. The classification of the hydrometeors (using the disdrometer data) characterized the water droplet microphysics yielding consistent results when compared to the observed ZDR-R relation of the instantaneous rain rates. The DSGs changed from 0,187 to 2,375 for rain rates greater than 6 mm/hr with the largest drop concentration frequencies within the class 0,427 (diamters in mm) with 34.224 drops. There was also variability in the classes 1,187 - 2,124mm, with a total of 1.949 drops. For rain rates greater than 2 mm/hr and smaller than 6mm/hr, drops with diameters greater than 1mm were detected, totaling 126 drops with diameters within the 0,187 - 1,375 mm interval; the largest drop concentration frequency occurred in the diameter class of 0,427 mm, with 79.785 drops. For rain rates less than 2mm/hr, the DSGs changed from 0,187 to 0,937 with the largest drop concentration frequency occurred in the diameter class of 0,312 mm, with 83.812 drops. There was only concentration of 13 drops in the diameter class of 0,937mm. The hydrometeors were from hot clouds associated with meso-scale systems (for example, sea/land breezes). The polarimetric ZDR-R relations appearing in the correlations showed less dispersion than the traditional Z-R relations, which presume good estimates in the rain iv quantification. Although the radar have overestimated the instantaneous rain rates during most of the period of the study maximum of 10,23 and minimum of 0,14), the polarimetric ZDR-R relations yielded good agreement between the estimated and observed instantaneous rates for the entire period, with RMSE of 1.00.